Prevalence of Trypanosomiasis of Wild Rats (Rattus sp.) in Banjarnegara District and Potential Impact for Public Health - Tri Wijayanti; Novia Tri Astuti; Nuri Alfino Qurana; Jarohman Raharjo; Bina Ikawati; Didik Tulus Subekti; Hari Ismanto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Trypanosomiasis is a zoonotic disease caused by Trypanosoma sp., a protozoan parasite that has a flagellum. It has the potential to cause emerging diseases. Generally, Trypanosoma infection is caused by T. evansi which causes Surra disease, and T. cruzi which causes Chagas disease. Trypanosoma lewisi has been considered a natural protozoan in mice, not pathogenic to humans but in recent years it has been reported in humans. This study aims to detect Trypanosoma in rats in Banjarnegara District and analyze the potential impact on public health. The research was observational with a descriptive approach, conducted in Banjarnegara from July-December 2020. Samples were taken by purposive sampling. Samples are rat’s blood that caught on wild rats survey in the main market of Banjarnegara District. Blood samples were made with a thin smear then they were stained with Giemsa and examined by microscope. There were 157 rats caught, consisting of 131 Rattus norvegicus and 26 R. tanezumi. Totally, 28 rats were positive Trypanosoma lewisi, so Trypanosoma infection in rats in Banjarnegara District is 16,57%. Trypanosomiasis in R. norvegicus was 18.3% and R. tanezumi 15.38%. Therefore, there is a need to increase the awareness of these diseases’s transmission to humans.